Carbohydrate effect: Hormone and oxidative changes - McAnulty, S.; McAnulty, L.; Nieman, D.; Morrow, J.; Dumke, C.; Utter, A. (International Journal of Sports Medicine, 2007)
Carbohydrate administration during exercise diminishes stress hormone release, but the relationship of these hormones with oxidative stress has not been examined. Fifteen subjects functioned as their own controls and ingested carbohydrate (6 %) or placebo in a randomized design while cycling for 2.5-h (~ 75 % V·O2peak). Blood and skeletal muscle samples were collected 30 min pre-exercise, immediately post-exercise, and 12-h post-exercise and analyzed for F2-isoprostanes, ferric reducing ability of plasma, glucose, insulin, cortisol, epinephrine, and muscle glycogen, respectively. Statistical design was a 2 (treatment) × 3 (time) repeated measures analysis of variance. Glucose, insulin, and ferric reducing ability of plasma were significantly higher and F2-isoprostanes, cortisol, and epinephrine significantly lower in carbohydrate versus placebo. The decrease in muscle glycogen was not different. During cycling exercise, oxidative stress appears to be heavily influenced by carbohydrate ingestion and increased stress hormones.